Theragnostic applications of mammal and plant-derived extracellular vesicles: latest findings, current technologies, and prospects - Ali, Nada Basheir; Abdull Razis, Ahmad Faizal; Ooi, Der Jiun; Chan, Kim Wei; Ismail, Norsharina; Foo, Jhi Biau (Multidisciplinary Digital Publishing Institute, 2022)
The way cells communicate is not fully understood. However, it is well-known that extracellular vesicles (EVs) are involved. Researchers initially thought that EVs were used by cells to remove cellular waste. It is now clear that EVs function as signaling molecules released by cells to communicate with one another, carrying a cargo representing the mother cell. Furthermore, these EVs can be found in all biological fluids, making them the perfect non-invasive diagnostic tool, as their cargo causes functional changes in the cells upon receiving, unlike synthetic drug carriers. EVs last longer in circulation and instigate minor immune responses, making them the perfect drug carrier. This review sheds light on the latest development in EVs isolation, characterization and, application as therapeutic cargo, novel drug loading techniques, and diagnostic tools. We also address the advancement in plant-derived EVs, their characteristics, and applications; since plant-derived EVs only recently gained focus, we listed the latest findings. Although there is much more to learn about, EV is a wide field of research; what scientists have discovered so far is fascinating. This paper is suitable for those new to the field seeking to understand EVs and those already familiar with it but wanting to review the latest findings.